2010
DOI: 10.1007/s11771-010-0566-5
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous flying particle swarm optimization algorithm and its application to slope stability analysis

Abstract: A new version of particle swarm optimization (PSO) called discontinuous flying particle swarm optimization (DFPSO) was proposed, where not all of the particles refreshed their positions and velocities during each iteration step and the probability of each particle in refreshing its position and velocity was dependent on its objective function value. The effect of population size on the results was investigated. The results obtained by DFPSO have an average difference of 6% compared with those by PSO, whereas D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…With the increasing complexity, the search algorithm tends to locate the local minimum instead of global minimum (i.e., local minima issue). To properly address the local minima issue, several heuristic optimization algorithms such as improved Harmony search algorithm [43,44] and discontinuous flying particle swarm optimization algorithm [45] have been proposed and used in deterministic slope stability analysis. e local minima issue arises in Slide 5.0 when the path search method with 10,000 potential failure surfaces cannot find the global minimum FS.…”
Section: Ree Numerical Procedures For the Calculation Of Fsmentioning
confidence: 99%
“…With the increasing complexity, the search algorithm tends to locate the local minimum instead of global minimum (i.e., local minima issue). To properly address the local minima issue, several heuristic optimization algorithms such as improved Harmony search algorithm [43,44] and discontinuous flying particle swarm optimization algorithm [45] have been proposed and used in deterministic slope stability analysis. e local minima issue arises in Slide 5.0 when the path search method with 10,000 potential failure surfaces cannot find the global minimum FS.…”
Section: Ree Numerical Procedures For the Calculation Of Fsmentioning
confidence: 99%
“…An in-house Fortran-based software package for deterministic slope stability analysis has been developed and used successfully in previous studies (Li et al, 2010;Chu, 2011, 2014;Li et al, 2013aLi et al, , 2013b. The software package is equipped with HS algorithm and particle swarm optimization algorithm for efficient location of the deterministic critical slip surface.…”
Section: Software Package For Deterministic Stability Analysismentioning
confidence: 99%
“…Much attention has been focused on the issue of quantitative risk assessment of slope failure [3][4][5][6][7][8][9][10][11]. e failure probability and the consequence were evaluated based on the critical slip surface with the minimum factor of safety (FS) in most of the previous research [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Although the area (volume for 3D case) of sliding mass corresponding to the critical slip surface with the minimum FS can serve as an index to quantify the consequence of a slope failure, current studies have shown that the critical slip surface with minimum FS is only an initial location of a slope failure, and it cannot represent the whole process of a slope failure, including not only the initiation stage but also the propagation and the evolution stages [8].…”
Section: Introductionmentioning
confidence: 99%